2010
DOI: 10.1103/physrevd.82.104055
|View full text |Cite
|
Sign up to set email alerts
|

Singularity-free solutions for anisotropic charged fluids with Chaplygin equation of state

Abstract: We extend the Krori-Barua analysis of the static, spherically symmetric, Einstein-Maxwell field equations and consider charged fluid sources with anisotropic stresses. The inclusion of a new variable (tangential pressure) allows the use of a non-linear, Chaplygin-type equation of state with coefficients fixed by the matching conditions at the boundary of the source. Some physical features are briefly discussed.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
108
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 180 publications
(110 citation statements)
references
References 51 publications
2
108
0
Order By: Relevance
“…Let y = y 1 be the particular solution of the differential equation (14). Then y = y 1 U will be complete solution of the differential equation (14), where…”
Section: The Solutions For the Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Let y = y 1 be the particular solution of the differential equation (14). Then y = y 1 U will be complete solution of the differential equation (14), where…”
Section: The Solutions For the Modelmentioning
confidence: 99%
“…More recently, a comprehensive work on the influence of local anisotropy on the structure and evolution of compact object has been published by Herrera et al [9]. In this regard several recently performed anisotropic compact star models may be consulted for further reference [10][11][12][13][14][15][16][17][18]. We also note some particular work concerned with the anisotropic aspect in physical systems like Globular Clusters, Galactic Bulges, and Dark Halos in Refs.…”
Section: Introductionmentioning
confidence: 99%
“…However, Bowers and Liang [11] indicated that anisotropy might have non-negligible effects on such parameters like equilibrium mass and surface redshift. In connection to pressure anisotropy inside a compact star several recent theoretical investigations are available in the literature [12][13][14][15][16][17][18][19]. However, there is an exhaustive review on the subject of anisotropic fluids by Herrera and Santos [20] which provides almost all references until 1997 and hence may be looked at for further information.…”
Section: Introductionmentioning
confidence: 99%
“…In this connection some other work on the anisotropic compact star models can be found in Refs. [6][7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%